Facile synthesis of mesoporous SiO2 nanoparticles using the mobility differences of etchants - Lee, Yi Seul; Jang, Wooree; Koo, Hye Young; Choi, Won San (ROYAL SOC CHEMISTRY, 2015)
In this paper, we report the preparation of mesoporous silica nanoparticles (MSNPs) using the mobility differences of sulfonate or sulfate-containing materials as etchants. The MSNPs were synthesised by treating silica nanoparticles (SNPs) with styrene sulfonate (SS) or sodium dodecyl sulfate (SDS) under heat. The simple treatment of the SNPs with SS or SDS led to surface etching of the SNPs, resulting in surface roughening and pore generation within the silica structure. The surface structuring of the SNPs could also be controlled by varying the concentration of counter ions of the etchants. This one-step process is very simple, facile, and scalable. The MSNPs appeared almost transparent in an aqueous solution due to their unique surface morphology. The resulting MSNPs also exhibited excellent adsorption and desorption properties for toxic organic pollutants.
Keywords: SILICA NANOPARTICLES; HOLLOW SILICA; CHEMISTRY; NANOSPHERES; CATALYSTS; SURFACES; DELIVERY; RATTLE; SHELL